2013
DOI: 10.1186/1471-2156-14-65
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of the gentle Africanized honey bee population (gAHB) in Puerto Rico

Abstract: BackgroundThe Africanized honey bee is one of the most spectacular invasions in the Americas. African bees escaped from apiaries in Brazil in 1956, spread over Americas and by 1994 they were reported in Puerto Rico. In contrast to other places, the oceanic island conditions in Puerto Rico may mean a single introduction and different dynamics of the resident European and new-coming Africanized bees.To examine the genetic variation of honey bee feral populations and colonies from different locations in Puerto Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…Previously, even with only a few markers it was observed that two of eight microsatellite loci tested deviated from the expected allele frequencies based on an admixture model (Galindo-Cardona et al, 2013). We tested this hybrid mosaic hypothesis now with 917 markers across the genome and found 6.5% of the markers to deviate from the admixture model, demonstrating the "mosaic" characteristic.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Previously, even with only a few markers it was observed that two of eight microsatellite loci tested deviated from the expected allele frequencies based on an admixture model (Galindo-Cardona et al, 2013). We tested this hybrid mosaic hypothesis now with 917 markers across the genome and found 6.5% of the markers to deviate from the admixture model, demonstrating the "mosaic" characteristic.…”
Section: Discussionmentioning
confidence: 73%
“…This admixed population is part of the broader history of the accidental introduction of Africanized honey bees (AHB) to continental Brazil and later spread across the Neotropics and southern Nearctic. However, AHB's continental origin remains unknown and only one introduction event is thought to have occurred (see Rivera-Marchand et al, 2008;Galindo-Cardona et al, 2013). As part of this expansion and assisted by human transit, AHB arrived to Puerto Rico in 1994 (Cox, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the expansion of Africanized honey bees in the temperate region of the southern United States seems to have been greatly enhanced by the decimation of resident feral European honey bee colonies following the arrival of the Varroa mite (Pinto et al 2005). Similarly, in Puerto Rico, a genetically stable honey bee population has formed, with European-and Africanlike traits associated with Varroa resistance (Galindo-Cardona et al 2013). The reported spread of Africanized colonies in neotropical highlands (Quezada-Euán et al 2003;Kraus et al 2007) may have been helped by similar parasite-related events.…”
Section: Discussionmentioning
confidence: 99%
“…In at least one study, the aggressive response of Africanized honey bees was reduced by as much as 50 % via artificial selection (Guzman-Novoa and Page 1999). More recently, a colony-level study by Rivera-Marchand et al (2012) showed that aggressive response was reduced in colonies of Africanized honey bees in Puerto Rico (coined gAHB, gentle Africanized honey bee, Galindo-Cardona et al 2013). …”
Section: Introductionmentioning
confidence: 99%